2021
DOI: 10.5312/wjo.v12.i7.485
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodesis of the first metatarsophalangeal joint: The “when and how”

Abstract: Arthrodesis of the first metatarsophalangeal (MTP) joint has been established as the “gold standard” for the treatment of several first ray disorders, due to its perceived efficacy and the consistently reported good results in the literature. Arthrodesis is a commonly performed procedure for the treatment of end stage arthritis, rheumatoid arthritis with severe deformity, selected cases of severe hallux valgus (with or without signs of degenerative joint disease), as well as a salvage procedure after failed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…First metatarsophalangeal joint (FMPJ) arthrodesis is a commonly performed procedure for symptomatic end‐stage hallux rigidus (grades 3 and 4) [1, 2]. The procedure can also be considered in selected cases of severe hallux abducto valgus (HAV) deformity associated with degenerative joint disease and as a salvage option for previously failed first ray procedures [3]. Nix et al [4] found HAV occurrence in 23% of people aged 18 to 65 and 35.7% in those over 65.…”
Section: Introductionmentioning
confidence: 99%
“…First metatarsophalangeal joint (FMPJ) arthrodesis is a commonly performed procedure for symptomatic end‐stage hallux rigidus (grades 3 and 4) [1, 2]. The procedure can also be considered in selected cases of severe hallux abducto valgus (HAV) deformity associated with degenerative joint disease and as a salvage option for previously failed first ray procedures [3]. Nix et al [4] found HAV occurrence in 23% of people aged 18 to 65 and 35.7% in those over 65.…”
Section: Introductionmentioning
confidence: 99%
“…The metatarsal and phalanx bones’ shape are modelled as cylindrical. During arthrodesis in the standard fixation technique [ 35 ], the bones of the MTP-1 joint are brought closer to each other. However, due to the possible lack of congruency of the MTP-1 joint [ 36 ], an average small gap of 1 mm is assumed [ 32 , 37 ] between the metatarsal’s and phalanx’s cortical fracture bone fragments.…”
Section: Methodsmentioning
confidence: 99%
“…25 The incidence of nonunion is expected to be <10% based on existing literature. [31][32][33][34] (2) Malunion can occur due to improper alignment of the bones and/or poor patient compliance with postoperative care. The incidence of malunion is around 6.1% with most occurring dorsally (87.1%).…”
Section: Complicationsmentioning
confidence: 99%
“… Nonunion of the arthrodesis site can occur due to inadequate joint preparation or mechanical failure of the fixation construct 25 . The incidence of nonunion is expected to be <10% based on existing literature 31–34 Malunion can occur due to improper alignment of the bones and/or poor patient compliance with postoperative care.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation